Thermal Synthesis of Perchlorinated Oligosilanes: A Fresh Look at an Old Reaction. Issue 50 (9th August 2017) - Neumeyer, Felix; Schweizer, Julia I.; Meyer, Lioba; Sturm, Alexander G.; Nadj, Andor; Holthausen, Max C.; Auner, Norbert
Abstract: A combined experimental and theoretical study of the high‐temperature reaction of SiCl4 and elemental silicon is presented. The nature and reactivity of the product formed upon rapid cooling of the gaseous reaction mixture is investigated by comparison with the defined model compounds cyclo ‐Si5 Cl10, n ‐Si5 Cl12 and n ‐Si4 Cl10 . A DFT assessment provides mechanistic insight into the oligosilane formation. Experimental 29 Si NMR investigations, supported by quantum‐chemical 29 Si NMR calculations, consistently show that the reaction product is composed of discrete molecular perchlorinated oligosilanes. Low‐temperature chlorination is an unexpectedly selective means for the transformation of cyclosilanes to acyclic species by endocyclic Si−Si bond cleavage, and we provide a mechanistic rationalization for this observation. In contrast to the raw material, the product obtained after low‐temperature chlorination represents an efficient source of neo ‐Si5 Cl12 or the amine‐stabilized disilene EtMe2 N⋅ SiCl2 Si(SiCl3 )2 through reaction with aliphatic amines. Abstract : Old reaction, new tricks : A complex mixture of small oligosilanes is produced by quenching the thermal reaction of SiCl4 and elemental silicon. A combined theoretical and experimental reinvestigation of the long‐known (SiCl2 ) x synthesis sheds new light on the reaction product and its reactivity (see figure).